Advancing Young Learners’ Scientific Literacy Through School Media Resource Centres - Ekeh, Martin Chukwudi (Research in Social Sciences and Technology- OpenED Network, 2024)
This qualitative study explores the state of school media resource centres (SMRCs) and their impact on fostering scientific literacy among early-grade learners in Staff Primary Schools. Perspectives of primary school librarians were gathered through photovoice methodology and semi-structured interviews from four selected schools within Owerri Education Zone 1, Nigeria. Thematic analysis was employed to scrutinise the data, ensuring credibility and trustworthiness through member checking and triangulation. Findings reveal a glaring absence of functional SMRCs despite the presence of school libraries, impeding effective teaching and learning processes. Librarians expressed the significance of SMRCs in advancing scientific literacy, yet perceived constraints hinder their efficacy. Challenges include inadequate funding, technological infrastructure, security concerns, and outdated resources. Recommendations highlight the necessity for prioritised financing, professional development opportunities, and collaboration with external stakeholders to enhance SMRCs. Moreover, addressing electricity-related challenges, updating library collections, strengthening security measures, involving parents, and implementing talent development programmes are crucial. In conclusion, the absence of functional SMRCs in staff primary schools significantly impedes the progress and holistic development of scientific literacy of early-grade learners. Addressing these deficiencies is imperative to foster scientific literacy and ensure quality education in the 21st century.